2014
DOI: 10.1128/jcm.03533-13
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Feasibility Study To Assess External Quality Assessment Panels for Xpert MTB/RIF Assay in South Africa

Abstract: (1) or unacceptable (0); the overall panel performance score for the Vircell, CDC, GLI, and NHLS panels was 9 of 12, while the MMQCI panel scored 6 of 12 (owing to the need for cold chain maintenance). All panels showed good compatibility with Xpert MTB/RIF testing, and none showed PCR inhibition. The use of a liquid or dry matrix did not appear to be a distinguishing criterion, as both matrices had reduced scores on insufficient volumes, a need for extra consumables, and the ability to transfer to the Xpert M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Since more than 90% RIF resistant strains are also resistant to INH [7][8][9][10], determining the RIF resistant strains, using the gene X-pert assay a rapid and sensitive technique, is an alternative approach to detect MDR-TB [11,9,10], and this could be explained by rate of spontaneous mutation rate; in which INH target gene has 100 times higher rate of mutation than that of RIF target gene [12]. Therefore, in high MDR-TB burden countries, diagnosis of RIF resistant TB is regarded as MDR-TB [9]. Furthermore, almost one-tenth (9%) of new MDR-TB cases, are likely to convert to extensively drug-resistant TB (XDR-TB) [1,5,6] In Sub-Saharan Africa, the estimated MDRT-TB incidence is very high (14%) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Since more than 90% RIF resistant strains are also resistant to INH [7][8][9][10], determining the RIF resistant strains, using the gene X-pert assay a rapid and sensitive technique, is an alternative approach to detect MDR-TB [11,9,10], and this could be explained by rate of spontaneous mutation rate; in which INH target gene has 100 times higher rate of mutation than that of RIF target gene [12]. Therefore, in high MDR-TB burden countries, diagnosis of RIF resistant TB is regarded as MDR-TB [9]. Furthermore, almost one-tenth (9%) of new MDR-TB cases, are likely to convert to extensively drug-resistant TB (XDR-TB) [1,5,6] In Sub-Saharan Africa, the estimated MDRT-TB incidence is very high (14%) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified continuous performance monitoring as a valuable addition to quality monitoring. External quality assessment only provides a 'snapshot' of the laboratory's routine performance, and EQA reports are evaluated retrospectively [5]. In contrast, commercially available peer review programs allow for daily monitoring in real time of instrument performance.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been learnt from the implementation of Xpert MTB/RIF as summarised in Table 2 and includes [66, 67] cost and forecast models [68, 69], program interfacing [70], socio-economic trends [71], and quality assessment [72]. Additional innovations, being reported for the first time for possible TB control (currently, developed for GeneXpert instruments), is remote connectivity [73, 74].…”
Section: Who Endorsed Diagnostic Technologiesmentioning
confidence: 99%